Personalising library services in higher education : the boutique approach - Priestner, Andy.; Tilley, Elizabeth, 1959-. (Margraf : Margraf, 2012)
In an economic climate where cuts are becoming the norm, a 'boutique' library service may seem a contradiction. This book unpacks the boutique model and is supported by a variety of case studies reflecting international practice.
Introducing the boutique approach / Andy Priestner and Elizabeth Tilley -- Face-to-face value : personalised communication strategies / Andy Priestner -- Library space and designing for a boutique library service in the USA / Beatrice Pulliam -- Case studies : Section 1. Students as consultants : SKOLKOVO Moscow School of Management / Helen Edwards -- Research postcards at London School of Economics / Michelle Blake and Nicola Wright -- Boutique at the Faculty of Education / Angela Cutts -- Personal space for study : meeting real needs / Elizabeth Tilley -- Library technologies for boutique services / Tim Wales -- Maximising value, enhancing learning : boutique teaching and training / Chris Powis -- Digital literacy support for researchers : the personalised approach / Jane Secker -- Case studies : Section 2. A voice in the wilderness : personalised library services in a virtual environment / Margaret Westbury -- Integrating information skills into the curriculum : the next step / Veronica Lawrence -- Online outreach and tailored training : the English Faculty Library at Oxford University / Kerry Webb -- Boutique influences on structures and lifelong learning at Australian Catholic University / Tatum McPherson-Crowie -- Marketing personalised services / Emma Thompson -- The cost-effective service : is personalised possible? / Elizabeth Tilley -- Evaluating the impact of the boutique library / David Streatfield -- Implementing and managing boutique / Andy Priestner and Elizabeth Tilley.
Includes bibliographical references and index.
Keywords: Academic libraries; Libraries and colleges; Public services (Libraries); Academic libraries -- Case studies; Academic libraries -- Case studies